Hubungan Self Efficacy dan Dukungan Keluarga dengan Kecemasan Siswa pada Pelajaran Matematika Sekolah Menegah Atas Negeri 2 Sinabang - Mariatun Mariatun; Abdul Munir; Cut Metia (Universitas Medan Area, 2020)
The objective of this research was to find out (1) the correlation between the students’ self efficacy, their family support, and their math anxiety, (2) the correlation between the students’ self efficacy and their math anxiety, and (3) the correlation between the students’ family support and their math anxiety. A math anxiety scale, a self-efficacy scale, and a family support scale were used as the instruments in this quantitative research. The collected data were then analyzed by using multiple regression and partial correlation analyses. The results indicated that the students’ self efficacy and their family support were in a significant correlation with those students’ math anxiety. It was showed by the coefficient F = 12.239; R = .548 with p = 0.000 (p 0.01). Moreover, it was also found that there was a correlation between the students’ self efficacy and their math anxiety with coefficient rx1 – y = -0.543 with p 0.01. In addition, the students’ family support was correlated to their math anxiety with coefficient rx2 – y = -0.257 with p 0.01. The students’ self efficacy and their family support gave as much as 30% of the influence in which 29.5% of it was from the self efficacy variable while 6.6% of it was from the family support variable.